Masculinity Studies An Interdisciplinary Approach - Bhatti, Feyza (IntechOpen, 2022)
Masculinity Studies - An Interdisciplinary Approach brings together scholarly research on theoretical issues and empirical studies on men and masculinities from different parts of the world. The book reflects the need for future studies that follow interdisciplinary and intersectional approaches, together with profound engagement with feminist and queer studies to understand men and varying forms of masculinities that men learn, embrace and perform at global and local levels. The book will appeal to students, teachers and researchers in social sciences and humanities, as well as professionals, employers and practitioners. It is a vital resource for those interested in theoretical, practical, and cultural issues around men, boys, and gender in social sciences.